Internal and external load during 8 v 8, 5 v 5 and 3 v 3 in Chinese elite youth male football players - Li, Z.; Mao, L.; Krustrup, P.; Randers, M. B. (Biology of Sport, 2022)
Aim to investigate internal and external load in three different game formats (8 v 8, 5 v 5, 3 v 3 with 80 m2 per player) of small-sided games (SSG) in Chinese elite youth football players. Twenty-nine elite male football players (age: 18.3 ± 0.5 years (mean ± SD), height: 175 ± 6 cm, weight: 65.5 ± 6.3 kg) participated in randomized order in the three formats. Each session consisted of 20 min: 3 v 3 on a 24 × 20-m pitch, 5 v 5 on a 32 × 25-m pitch, or 8 v 8 on a 40 × 32-m pitch all equalling 80 m2 per player. Each player was recorded once in each format. Using GPS-units and heart rate belts and blood lactate measured the two kinds of load. 8-10% higher total distance (P < 0.01) was observed in 8 v 8 and 5 v 5 compared with 3 v 3 (1627 ± 240 and 1595 ± 243 m vs. 1477 ± 179 m, ES = 0.55-0.71). Higher distance (P < 0.001) was covered with high speed running (HSR: > 14 km/h) in 8 v 8 and 5 v 5 than 3 v 3 (154 ± 94 m and 133 ± 59 m vs. 77 ± 35, ES = 1.09-1.15), whereas very high speed running distance (> 21 km/h) was higher (P < 0.01) in 8 v 8 than 5 v 5 and 3 v 3 (15.2 ± 19.5 vs. 5.3 ± 6.7 and 1.0 ± 0.4 m, ES = 0.69-1.03) and in 5 v 5 than 3 v 3. No difference was found between game formats in the number of intense accelerations nor intense decelerations. Blood lactate (3.5 ± 2.3 vs. 2.8 ± 1.9 vs. 2.4 ± 1.5 mmol · L-1, P = 0.201) and mean heart rate (155 ± 21 vs. 160 ± 11 vs. 157 ± 17 bpm, P = 0.254) was not different between 8v8, 5v5 and 3v3 game formats. Distance covered in total and in highest speed zones was higher in SSG formats with more players, which, however, did not lead to differences in internal load measured by heart rate and blood lactate.